Pencegahan Penyalahgunaan Gadget dan Perlindungan Anak pada Siswa SMAIT Daarul’ Ilmi Bandar Lampung - Maroni, Maroni; Dewi, Erna; Fathonah, Rini; Warganegara, Damanhuri; Ariani, Nenny Dwi; Anwar, Mashuril (University of Merdeka Malang, 2020)
In general, the students at SMAIT Daarul Ilmi do not understand about the prevention of gadget abuse and child protection properly. They also have never received legal counseling regarding gadget abuse and child protection. Thus, it is necessary to provide good knowledge and understanding through socialization and focus group discussions (FGD) to overcome partner problems related to the prevention of gadget abuse and child protection among students of SMAIT Daarul Ilmi, Bukit Kemiling Permai, Bandar Lampung City. This program includes providing knowledge and understanding, prevention of gadget abuse, and child protection. Then proceed with discussion and question and answer, and test the participants' understanding by giving a pre-test and post-test. The results of the program show that this socialization and focus group discussion (FGD) activity is important to increase public knowledge, understanding and legal awareness regarding the prevention of gadget abuse and child protection. This program contributes to preventing the adverse effects of technological change.DOI:Â https://doi.org/10.26905/abdimas.v5i3.3405Â